The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1016/s0092-8674(02)01116-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Signaling Network in Lateral Nucleus of Amygdala Important for Inhibiting Memory Specifically Related to Learned Fear

Abstract: We identified the Grp gene, encoding gastrin-releasing peptide, as being highly expressed both in the lateral nucleus of the amygdala, the nucleus where associations for Pavlovian learned fear are formed, and in the regions that convey fearful auditory information to the lateral nucleus. Moreover, we found that GRP receptor (GRPR) is expressed in GABAergic interneurons of the lateral nucleus. GRP excites these interneurons and increases their inhibition of principal neurons. GRPR-deficient mice showed decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
289
7
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(320 citation statements)
references
References 48 publications
23
289
7
1
Order By: Relevance
“…Our results support this expectation, since LTP was generated by a stimulation paradigm that was insufficient in control animals. The mechanism for the facilitation of LTP induction appears straightforward: if GABAergic inhibition of responses to cortical input is depressed (dysinhibiton), the probability of coincidence between postsynaptic depolarisation and presynaptic activation should increase, which in terms of spike timing explains sustained potentiation of the synaptic response (Shumyatsky et al, 2002). Indeed, the facilitatory effect of GABAergic suppression on LTP induction has been previously demonstrated (Watanabe et al, 1995;Rammes et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results support this expectation, since LTP was generated by a stimulation paradigm that was insufficient in control animals. The mechanism for the facilitation of LTP induction appears straightforward: if GABAergic inhibition of responses to cortical input is depressed (dysinhibiton), the probability of coincidence between postsynaptic depolarisation and presynaptic activation should increase, which in terms of spike timing explains sustained potentiation of the synaptic response (Shumyatsky et al, 2002). Indeed, the facilitatory effect of GABAergic suppression on LTP induction has been previously demonstrated (Watanabe et al, 1995;Rammes et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Also, in slices of the BLA obtained from DZM withdrawn animals stimuli were applied to cortical afferents to the BLA contained in the external capsule (EC) (De Olmos et al, 1985;Fisk and Wyss, 2000). A growing amount of evidence indicates that the synaptic modifications in the BLA, which accompany behavioral learned fear, are mechanistically similar to long-term potentiation (LTP) evoked by electric stimulation in amygdala slices (Shumyatsky et al, 2002). Given that in vitro and in vivo studies have strongly suggested that the BLA could be a locus of synaptic neuroplasticity -such as LTP -and that this process is required to store pavlovian aversive learning (McKernan and Shinnick-Gallagher, 1997;Quirk et al, 1995;Rogan and LeDoux, 1995;Fanselow and Ledoux, 1999;Maren, 1999;LeDoux, 2000;Doyère et al, 2003), we also evaluated whether prior BDZ withdrawal affects the induction of LTP in the BLA following highfrequency stimulation (HFS) of the EC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support the central role GABA neurotransmission has in extinction, however, there are different reports regarding the role of GABA in extinction (Harris and Westbrook, 1998;Marsicano et al, 2002;McGaugh et al, 1990;Pereira et al, 1988Pereira et al, , 1989Shumyatsky et al, 2002). Systemic administration of the GABA A antagonist picrotoxin after the extinction of inhibitory avoidance learning enhanced extinction retention during testing (McGaugh et al, 1990), and the GABA A -positive allosteric modulator diazepam impaired extinction retention when administered before extinction in a shuttle avoidance task (Pereira et al, 1989).…”
Section: Gaba a In Amygdala And Cta Extinctionmentioning
confidence: 99%
“…Additionally, Shumyatsky et al (2002) found that gastrin-releasing peptide (GRP) receptor-deficient mice showed decreased inhibition of principal neurons through the GABAergic interneurons in the amygdala and showed impaired extinction of long-term fear memory. More recently, Chhatwal et al (2005) showed that gephyrin mRNA and protein levels in the BLA significantly increased after fear extinction training, suggesting that the modulation of gephyrin and GABA A receptor expression in the BLA may play a role in the experience-dependent plasticity underlying extinction.…”
Section: Gaba a In Amygdala And Cta Extinctionmentioning
confidence: 99%
“…Axons from these LA neurons project to other nuclei of the amygdala (LeDoux, 2000), as well as to local circuit interneurons. Neurotransmitters and neuromodulators, such as norepinephrine, dopamine, serotonin, acetylcholine, gastrinreleasing peptide, vesicular zinc, and cholecystokinin may modulate the relative state of amygdalar activity (LeDoux, 2000;Shumyatsky et al, 2002;Bissiere et al, 2003;Kodirov et al, 2006;Meis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%